DIMENSI DAN SISTEM PERAKARAN SENTANG (Azadirachta excelsa Jack.) DALAM SISTEM AGROFORESTRI DENGAN MENIRAN (Phyllanthus sp.) Dimension and Rooting System of Sentang (Azadirachta excelsa Jack) in Agroforestry with Meniran (Phyllanthus sp.) - Nilasari Dewi; Nurheni Wijayanto; Gusmaini . (Jurnal Silvikultur Tropika, 2018)
Sentang (Azadirachta excelsa) is one of fast-growing tree species which is resistant to disease and pest. It also has good quality of timber with high economic value. Sentang planting can be integrated with meniran (Phyllanthus sp.). Planting in the agroforestry system will impact positively and negatively to both plants. The aim of this research was to analyze growth of sentang in agroforestry system. This research was conducted in Cultivation for Conservation Unit of Medicinal Plants Biofarmaka, IPB, Dramaga, West Java, Indonesia. The experimental design used was a completely randomized design to analysis sentang growth. The treatment applied was P0= monoculture and P1 = agroforestry. The total height growth and total stem diameter on monoculture are not significantly different with agroforestry. However, the high growth of sentang on the agroforestry was higher than monoculture in the first month, and the stem diameter on the agroforestry system was lower in the second month. Agroforestry systems do not provide any real effect on the growth of the canopy and rooting sentang except in diameter of root.Keywords: agroforestry, Azadirachta excelsa, plant dimension, rooting system